Nilai Ikonik: Packaging pada â€œAngkot Gaulâ€ Kota Padang - Masful, Mila Falma (Faculty of Communications Science, Dr. Soetomo University, 2017)
Today, there are many advanced transportation tools developed and created by humans in order to meet all the elements of satisfaction in the human self itself. As in Indonesia itself recently will be built rapid train from Jakarta to the city of Bandung. This is one of the qualified facilities that are expected to fulfill the needs of the society in transportation. But behind it all there are some means of transportation where people are not too interested in all sophistication of technology, but has an artistic, iconic and unique value to use.